Contrasting Volcanic Deformation in Arc and Ocean Island Settings Due To Exsolution of Magmatic Water. (21st July 2022) - Yip, Stanley Tze Hou; Biggs, Juliet; Edmonds, Marie; Liggins, Philippa; Shorttle, Oliver
Abstract: Two of the most widely observed co‐eruptive volcanic phenomena—Ground deformation and volcanic outgassing—Are fundamentally linked via the mechanism of magma degassing and the development of compressibility, which controls how the volume of magma changes in response to a change in pressure. Here we use thermodynamic models—Constrained by petrological data—To reconstruct volatile exsolution and the consequent changes in magma properties. We use the fraction of SO2 exsolved during decompression to predict co‐eruptive SO2 flux and magma compressibility to predict co‐eruptive surface deformation (both normalized by erupted volume). We conduct sensitivity tests using properties of typical basalts to assess how varying magma volatile content, crustal properties, and chamber geometry affect co‐eruptive deformation and degassing. We find that magmatic H2 O content has the most impact on both SO2 flux and volume change. Our findings have general implications for typical basaltic systems in arc and ocean island settings. The higher water content of arc magmas makes them more compressible than ocean island magmas and leads to muted or non‐existent deformation being observed during arc eruptions. Our models are consistent with observation: Deformation has been detected during 48% of basaltic eruptions in ocean island settings (16/33) during the satellite era (2005–2020), but only 11% of basaltic eruptions in arc settings (7/61). Plain Language Summary: Volcano monitoring provides a wealth of data upon which to base activity forecasts, yet we lack quantitative models to integrate two of the most widely observed eruptive parameters: Ground deformation and volcanic gas fluxes. When magma exsolves volatiles (water, carbon dioxide, sulfur) during storage in the crust prior to eruptions, the fluid bubbles cause the magma to become compressible, and behave like a sponge. The effect of this degassing is that when pressure changes in the magma chamber (due to eruption, or due to recharge), the gas bubbles expand or contract in response, effectively maintaining a near‐constant volume for the magma. Understanding the effect of magmatic gas on volume changes is key to developing integrated, satellite‐based volcano monitoring approaches. Key Points: We use petrological data and a thermodynamic framework to model volcanic deformation and SO2 degassing We compiled observations from 94 basaltic eruptions and did a systematic study of parameter space including H2 O content High magmatic volatile content contributes to the lack of deformation observed during arc basalt eruptions